Infectious screening and vaccination coverage in patients with inflammatory bowel disease: a single-center observational study - Banasik, Estera; Dobrowolska, Agnieszka; Roszak, Magdalena; Eder, Piotr (Folia Medica Cracoviensia, 2026)
Introduction: Patients with inflammatory bowel disease (IBD) are at increased risk of infections due to immune dysfunction and use of immunosuppressive and biologic therapies. Therefore, proper screening for latent infections and vaccinations are important to improve treatment safety. The aim of the study was to assess serological screening for hepatitis B and C virus (HBV, HCV) infections and to evaluate vaccination coverage in patients with IBD in routine clinical practice in a tertiary center. Materials and Methods: A total of 105 patients with IBD were included (Crohn’s disease, n = 56; ulcerative colitis, n = 48; IBD unclassified, n = 1). Data were collected using an original questionnaire and laboratory assessment of HBV and HCV markers. A subgroup analysis evaluated COVID-19 vaccination and adverse events. Results: All patients reported a negative history of HBV and HCV infection. Anti-HBc total antibodies were detected in 5 patients, while none were HBsAg-positive and none tested positive for anti-HCV antibodies. Among 82 patients vaccinated against HBV, 31 (38%) had nonprotective anti-HBs titers. Current IBD treatment was not associated with impaired vaccine response. Vaccination rates for influenza, pneumococci, and meningococci were low. Only 15% of patients reported receiving information about vaccination from the physicians. In the COVID-19 subgroup, 74.7% of patients were vaccinated, with mostly mild adverse events. Conclusions: Despite existing recommendations, screening and vaccination coverage in patients with IBD remain insufficient, indicating the need for implementation of immunoprophylaxis in routine clinical practice.